Влияние скорости нагрева токами высокой частоты доэвтектной стали на кинетику ɑ → ɣ превращения - Яковлев, Ф. И.; Маршуба, Вячеслав Павлович (НТУ "ХПИ", 2003)
The results of the investigations on influencing the speed of heating by currents of high frequency of the steel on kinetics ɑ → ɣ of transformation are considered in the article. The given results helper to define the dependence ɑ → ɣ of transformation for the speed of steel heating by currents of high frequency.
Keywords: закалка токами; мартенсит; аустенит; температура; феррит; микроструктура